2020
DOI: 10.1136/svn-2019-000278
|View full text |Cite
|
Sign up to set email alerts
|

Different contribution of SBP and DBP variability to vascular events in patients with stroke

Abstract: BackgroundHigh blood pressure variability (BPV) is a novel risk factor for cardiovascular disease. However, the heterogeneity of systolic blood pressure variability (SBPV) and diastolic blood pressure variability (DBPV) for different vascular events remains unclear. This study aims to investigate whether SBPV or DBPV has different contribution to vascular events in patients with acute ischaemic stroke (IS) or transient ischaemic attack (TIA). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…Our finding was consistent with the post hoc analysis of the Blood Pressure and Clinical Outcome in TIA and IS trial (BOSS), in which cardiovascular events were only related to diastolic BPV (defined as the SD and coefficient of variation of the DBP) rather than systolic BPV in patients with a history of ischemic stroke and transient ischemic attack. 22 Similar findings were also reported in the Action to Control Cardiovascular Risk in Diabetes trial (ACCORD) in which diastolic BPV was strongly associated with coronary heart disease, especially in patients with a low baseline BP. 23 In addition, diastolic BPV has been reported as a risk factor for cognitive decline and stroke recurrence.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our finding was consistent with the post hoc analysis of the Blood Pressure and Clinical Outcome in TIA and IS trial (BOSS), in which cardiovascular events were only related to diastolic BPV (defined as the SD and coefficient of variation of the DBP) rather than systolic BPV in patients with a history of ischemic stroke and transient ischemic attack. 22 Similar findings were also reported in the Action to Control Cardiovascular Risk in Diabetes trial (ACCORD) in which diastolic BPV was strongly associated with coronary heart disease, especially in patients with a low baseline BP. 23 In addition, diastolic BPV has been reported as a risk factor for cognitive decline and stroke recurrence.…”
Section: Discussionsupporting
confidence: 79%
“…23 In addition, diastolic BPV has been reported as a risk factor for cognitive decline and stroke recurrence. 9,22,24 These findings might indicate that diastolic BPV becomes more important for older adults with hypertension and that it is essential to monitor the DBP in older adults. The underlying mechanism for the significance of diastolic BPV in older adults might be the fluctuation and reduction of coronary perfusion during diastole, which leads to coronary hypoperfusion and exacerbates myocardial ischemia.…”
Section: Discussionmentioning
confidence: 98%
“…The reversion of increased BP by HEP supplementation was more evident for DBP since the CRP group under SD displayed significantly lower values than the CR group. It can be noted that the repercussion of SBP and DBP in cardiovascular disease development may be different; e.g., variability in DBP has been recently suggested as a more important predictor of cardiovascular adverse events than SBP in certain patients (with stroke), and DBP and isolated diastolic hypertension seem to be more related to the drive of coronary risk in younger subjects. , Moreover, the pectin-supplemented animals showed a higher percentage of heart weight than both C and CR animals. Although cardiac hypertrophy is usually considered a risk factor, the surrounding observed physiological conditions suggest that such increase in the relative heart weight might be associated with a favorable cardiovascular profile, as may happen, for instance, in trained athletes …”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that SBP was associated with stroke recurrence[ 25 ]. Turana et al [ 26 ] also found that SBP was positively correlated with stroke incidence, and adherence to hypertension treatment is to be the main goal in the prevention of stroke occurrence in several countries in Asia.…”
Section: Discussionmentioning
confidence: 99%